(3JMOjGJ GdJfejI ef hge GdJMQQ GdGbJUGOj Gdi HfGA eLJeY HOjd (B/s - (3dGJhT, SjQLs ((3HjQhJ(B: s (3GdTQcI GdYGdejI ddcJGH(B, s, 2007)
(3jJfGhd GdcJGH GdLGfH GLJeGYj, GfSGfj, eMdj, OGFe(B... (3JLedJ GdJfejI aj GdaJQI GdGNjQI H` (B"(3KjGH LejdI(B"(3, JJdGAe eY eYGjjQ GdefXeGJ GdOhdjI eKd GdHfc GdOhdj hUfOhb GdfbO GdOhdj(B. (3dcf GdefWb GdGbJUGOj Hbj Ydi MGdg hfehPL GdJfejI eWGHbkG dBQGA GddjHQGdjI GdLOjOI GdJbdjOjI(B. (3hGdMGdI gPg, aEf GdhVY GdJfehj jQJcR Gdi eYJbOGJ GNQhjI JaJQV GecGfjI JCejf GdQNGA GdeGOj ddLejY aj Mjf Gf GdMbGFb cTaJ Gf eKd gPg GdeYJbOGJ eOeQI dOQLI dG jecf Cf JMJed GdCQV chGQKgG(B. (3EPkG, dG HO ef GYGOI GdfXQ hHWQjbI fbOjI aj eaGgje GdJfejI, GdMGLGJ GdVQhQjI, hESbGW eNjdJfG GdGbJUGOjI, HeG jDOj HGdJGdj Gdi GdZGA GdeaGgje GdZQHjI hGdYhdeI(B. (3HGdJCcjO dG JMed OYhJfG YhOI eSJMjdI Gdi GdhQGA, EfeG GHJcGQ GTcGd LOjOI dJfejI HOjdI, hJMOjOkG GdYhOI Gdi GdJfejI GdTYHjI GdeMdjI hHeG jJdGAe eY eJWdHGJ hJWdYGJ cd eLJeY(B. s
(3HjHdjhZQGajG U(B.95s
Keywords: (3GbJUGOs; (3GdJHYjI GdGbJUGOjIs; (3JfejI (B- (3JNWjW GbJUGOjs